2019
DOI: 10.1080/10408398.2019.1646703
|View full text |Cite
|
Sign up to set email alerts
|

How processing may affect milk protein digestion and overall physiological outcomes: A systematic review

Abstract: Dairy is one of the main sources for high quality protein in the human diet. Processing may, however, cause denaturation, aggregation, and chemical modifications of its amino acids, which may impact protein quality. This systematic review covers the effect of milk protein modifications as a result of heating, on protein digestion and its physiological impact. A total of 5363 records were retrieved through the Scopus database of which a total of 102 were included. Although the degree of modification highly depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
108
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(114 citation statements)
references
References 126 publications
0
108
0
6
Order By: Relevance
“…Consequently, this leads to a direct hindrance of the proteolytic cleavage sites [28,29]. Additionally, indirect steric hindrance of the proteolytic cleavage sites can occur through binding to residues close to proteolytic cleavage sites, or it can cause cross-linking that inhibits access for proteases [26]. Alternatively, glycation may also promote proteolysis by opening up the tertiary structure of proteins (conjugation may interfere with refolding the protein after heating [29]), which was observed in the study by Moscovici [24].…”
Section: Digestion Of Agesmentioning
confidence: 96%
See 1 more Smart Citation
“…Consequently, this leads to a direct hindrance of the proteolytic cleavage sites [28,29]. Additionally, indirect steric hindrance of the proteolytic cleavage sites can occur through binding to residues close to proteolytic cleavage sites, or it can cause cross-linking that inhibits access for proteases [26]. Alternatively, glycation may also promote proteolysis by opening up the tertiary structure of proteins (conjugation may interfere with refolding the protein after heating [29]), which was observed in the study by Moscovici [24].…”
Section: Digestion Of Agesmentioning
confidence: 96%
“…In addition to the above mentioned experimental studies, an excellent systematic review by van Lieshout et al (2019) analysing the effects of glycation on protein digestibility concluded that glycation decreases protein digestibility [26]. One explanation for the reduction of protein digestibility by the MR lies in the nature of the reaction itself.…”
Section: Digestion Of Agesmentioning
confidence: 99%
“…However, most in vitro and animal studies on (isolated) milk proteins that focus more specifically on the effect of glycation suggest that lysine blockage impairs protein digestibility. 4 True ideal digestibility of lysine and other amino acids was reduced in rats when feeding a heated mixture of lactic casein or skimmed milk powder with lactose compared to when feeding a non-heated mixture. 5,6 Furthermore, a study in pigs demonstrates that 50% blockage of lysine in skimmed milk powder results in a significant decrease in post-prandial plasma appearance of lysine and total amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Maintaining Maillard reaction products as low as technically feasible is acknowledged as having a role in protein digestibility [15,16]. A recent systematic review by van Lieshout GAA et al concludes that glycation decreases protein digestibility and lowers amino acid availability, especially for lysine [36]. Undigested glycated protein can escape intestinal digestion and end up in the distal ileum and colon.…”
Section: Discussionmentioning
confidence: 99%